Asian Countries and Arctic Shipping: Policies, Interests and Footprints on Governance - Moe, Arild; Stokke, Olav Schram (Arctic Review on Law and Politics, 2019)
Most studies of Asian state involvement in Arctic affairs assume that shorter sea-lanes to Europe are a major driver of interest, so this article begins by examining the prominence of shipping concerns in Arctic policy statements made by major Asian states. Using a bottom-up approach, we consider the advantages of Arctic sea routes over the Suez and Panama alternatives in light of the political, bureaucratic and economic conditions surrounding shipping and shipbuilding in China, Japan and the Republic of Korea. Especially Japanese and Korean policy documents indicate soberness rather than optimism concerning Arctic sea routes, noting the remaining limitations and the need for in-depth feasibility studies. That policymakers show greater caution than analysts, links in with our second finding: in Japan and Korea, maritime-sector bureaucracies responsible for industries with Arctic experience have been closely involved in policy development, more so than in China. Thirdly, we find a clear tendency towards rising industry-level caution and restraint in all three countries, reflecting financial difficulties in several major companies as well as growing sensitivity to the economic and political risks associated with the Arctic routes. Finally, our examination of bilateral and multilateral Chinese, Japanese and Korean diplomatic activity concerning Arctic shipping exhibits a lower profile than indicated by earlier studies.